Social capital, philantrophy, Go-Ngo relations and community development - Anonuevo, Augustus T. (2010)
The potential of overseas Filipino migration to contribute to community development remains largely untapped. Philanthropic contributions, investments, and transfer of knowledge and skills of overseas Filipinos should be tapped for community development. Overseas Filipinos and their organizations as development resource and form of social capital must be transformed as strategic philanthropy that invests, not only in charitable activities but more importantly, in long term and sustainable dent in community development efforts, two other forms of social capital must also be transformed namely, community organizations into social enterprises and NGOs and GOs into strong partnerships for community development.

Philantrophic and other contributions of the Filipino diaspora, viable social enterprises, and strong NGO-GO partnership are identified as key elements of a proposed model for community development. The experiences of two NGOs, namely Atikha and Unlad Kabayan serve as illustrations of the use of overseas Filipinos' savings and investments in establising social enterprises in communities. They also show the rich potential of working with local government units, other government agencies, and overseas Filipino organizations on community development projects.
Keywords: Overseas migration